(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2022)
In this article, the particle swarm optimization toll (PSOT) is proceeded for solving the online parameters estimation of PMSM. The estimation procedure is depending on the real measurement of motor current and speed. The competitive algorithms are assessed in terms of the closeness between estimated and actual parameters’ which is considered the main target to be optimized in this work. Experimental verifications are carried out on Ecole Centrale de Nantes laboratories. The calculated results signify the effectiveness and reliability of the suggested tool. According to the results obtained, PSO has the capability and stability to calculate optimal values of PMSM parameters and then can calculate the performance of PMSM. The suggested PSO optimization tool leads to the highest closeness between estimated and experimental-based parameters. In addition, the POT is the outperformance optimization algorithm that gives the best values between the estimated and actual parameters.